2018
DOI: 10.1111/acer.13877
|View full text |Cite
|
Sign up to set email alerts
|

A Unifying Hypothesis Linking Hepatic Adaptations for Ethanol Metabolism to the Proinflammatory and Profibrotic Events of Alcoholic Liver Disease

Abstract: The pathogenesis of alcoholic liver disease (ALD) remains poorly understood but is likely a multihit pathophysiological process. Here, we propose a hypothesis of how early mitochondrial adaptations for alcohol metabolism lead to ALD pathogenesis. Acutely, ethanol (EtOH) feeding causes a near doubling of hepatic EtOH metabolism and oxygen consumption within 2 to 3 hours. This swift increase in alcohol metabolism (SIAM) is an adaptive response to hasten metabolic elimination of both EtOH and its more toxic metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 233 publications
(319 reference statements)
0
33
0
2
Order By: Relevance
“…Most studies of acute alcoholic liver damage have been performed in rodent models, which often divided into three types: single binge, intermittent heavy drinking and chronic alcohol exposure followed by episodes of binge, but there is no generally accepted method to date [ 26 , 31 , 32 ]. It was found that ethanol was administered at doses of 6–7 g/kg in rodents that produced peak blood ethanol concentrations that are similar to those that might be present in humans during acute alcoholism, which took into account differences in alcohol metabolism between rodents and humans [ 26 , 33 , 34 ]. Various factors cause abnormal lipid accumulation in lipid droplets in the liver, known as hepatic steatosis, which is the first and most common hepatic change induced by alcohol consumption [ 26 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies of acute alcoholic liver damage have been performed in rodent models, which often divided into three types: single binge, intermittent heavy drinking and chronic alcohol exposure followed by episodes of binge, but there is no generally accepted method to date [ 26 , 31 , 32 ]. It was found that ethanol was administered at doses of 6–7 g/kg in rodents that produced peak blood ethanol concentrations that are similar to those that might be present in humans during acute alcoholism, which took into account differences in alcohol metabolism between rodents and humans [ 26 , 33 , 34 ]. Various factors cause abnormal lipid accumulation in lipid droplets in the liver, known as hepatic steatosis, which is the first and most common hepatic change induced by alcohol consumption [ 26 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of ALD is multifaceted and includes both direct and indirect factors, such as hepatocyte toxicity derived from ethanol (EtOH) metabolism, oxidative stress, DNA damage, metabolic alterations, and inflammation. Central to these disease processes is mitochondrial dysfunction which has been shown to be critical during both the onset and progression of ALD (Zhong and Lemasters, ). Mitochondria are essential organelles for the preservation of cell homeostasis.…”
mentioning
confidence: 99%
“…Nonetheless, in ALD, there is an increase in the metabolization of ethanol to acetaldehyde by the cytosolic enzyme ADH and then from acetaldehyde to acetate by the mitochondrial enzyme aldehyde dehydrogenase [11] . In the long run, this will generate mitochondrial dysfunction, which is considered a critical step for the onset and progression of ALD [12] . Dysfunctional mitochondrial can undergo a fragmentation pathway to further be cleared by autophagy or promote the apoptotic cascade in sever liver injury by a multi-step process called "mitochondrial dynamics" controlled by the activity of the mitochondria shaping proteins (MSP) [13] .…”
Section: Alcoholic Liver Disease and Hccmentioning
confidence: 99%